2022
DOI: 10.3390/ijerph192113993
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors and Their Impact on Mental Health in Public Safety Organizations

Abstract: Public safety personnel (PSP), including correctional officers, firefighters, paramedics, and police officers, have higher rates of mental health conditions than other types of workers. This scoping review maps the impact of organizational factors on PSP mental health, reviewing applicable English language primary studies from 2000–2021. JBI methodology for scoping reviews was followed. After screening, 97 primary studies remained for analysis. Police officers (n = 48) were the most frequent population studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 116 publications
1
16
0
Order By: Relevance
“…This was reflected in the data among the PSP stakeholders, as it pertained to PSP's role in operating the respective RPs. Adequate staffing levels, along with co-worker and supervisor support, are positive organizational factors that facilitate better mental health among PSP organizations (Edgelow et al, 2022). Additionally, the sub-theme of, "the right people for the job," has been found in previous literature regarding the RP Facilitator Training Program (Jones et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This was reflected in the data among the PSP stakeholders, as it pertained to PSP's role in operating the respective RPs. Adequate staffing levels, along with co-worker and supervisor support, are positive organizational factors that facilitate better mental health among PSP organizations (Edgelow et al, 2022). Additionally, the sub-theme of, "the right people for the job," has been found in previous literature regarding the RP Facilitator Training Program (Jones et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Participants noted that a lack of attention to the evolving staffing needs and operational demands within the RP could be a major threat to the programs and potentially contribute to OSIs among RP staff themselves. A recent literature review addressing the impact of organizational factors on the mental health of PSP organizations found that high workload and limited resources were negative organizational factors frequently cited by paramedics and firefighters that contribute to negative mental health outcomes (Edgelow et al, 2022). This was reflected in the data among the PSP stakeholders, as it pertained to PSP's role in operating the respective RPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, little is known about the experiences of PSP who have made this type of WSIB claim. A recent survey-based study of 145 Ontario PSP who had an approved WSIB mental stress injury claim explored this experience with a focus on the RTW process (Edgelow et al, 2023b). The study revealed that the most frequently accessed healthcare providers were psychologists (61%), occupational therapists (60%), and general practitioners (44%).…”
Section: Introductionmentioning
confidence: 99%